Analisis Pembentukan Portofolio Saham Menggunakan Model Indeks Tunggal pada Saham Indeks LQ-45 Periode Januari 2013 sampai dengan Juli 2016 di Bursa Efek Indonesia - Fithriya Zahra (Jurnal Sekretaris dan Administrasi Bisnis, 2017)
The purpose of this study is to determine the shares of Stock Index LQ 45 members that form the optimal portfolio when used Single Indeks Model. The method used in this research is descriptive method of analysis. Data used are secondary data. Sampling in this research is purposive sampling, Sample is determined by criteria that these stocks are in a row included within Index LQ-45 for the period of observations. Results of analysis showed that using Single Indeks Model are selected to form the optimal portfolio the period January 2013 – July 2016 is there is a combination of four stocks is a leading and shaping the portfolio. Fourth shares were PT. Gudang Garam Tbk (GGRM), Cenral Bank Asia, Tbk (BBCA), Bank Negara Indonesia Tbk (BBNI), and Perusahaan Gas Negara (Persero) Tbk (PGN). Keywords: Portofolio, Single Indeks Model, LQ-45